2010
DOI: 10.1186/1756-9966-29-87
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone and cisplatin as a therapeutic combination in lung cancer: In vitro and in vivo

Abstract: BackgroundThymoquinone (TQ) is a compound extracted from Black Caraway seeds of Nigella Sativa and is active against various cancers. Cisplatin (CDDP) is the most active chemotherapeutic agent in Lung Cancer. Here we report activity of TQ against non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) cell lines alone and in combination with Cisplatin (CDDP).MethodsFor proliferation MTT assay, cell viability trypan blue assay and for apoptosis Annexin-V FITC assay were used in NCI-H460 and NCI-H14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
130
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(140 citation statements)
references
References 27 publications
5
130
2
3
Order By: Relevance
“…This was demonstrated with proliferation assays in two HNSCC cell lines. These results differ from previous findings (14,16). Jafri et al (16) combined TQ with cisplatin in lung cancer cell lines (NCI-H460 and NCI-H146) in vitro and in a mouse xenograft model using NCI-H460 in vivo.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This was demonstrated with proliferation assays in two HNSCC cell lines. These results differ from previous findings (14,16). Jafri et al (16) combined TQ with cisplatin in lung cancer cell lines (NCI-H460 and NCI-H146) in vitro and in a mouse xenograft model using NCI-H460 in vivo.…”
Section: Discussioncontrasting
confidence: 57%
“…These results differ from previous findings (14,16). Jafri et al (16) combined TQ with cisplatin in lung cancer cell lines (NCI-H460 and NCI-H146) in vitro and in a mouse xenograft model using NCI-H460 in vivo. The study described a synergistic effect of the combination treatment and concluded that TQ and cisplatin appear to be an active therapeutic combination in lung cancer.…”
Section: Discussioncontrasting
confidence: 57%
“…Recent studies indicate that N sativa extracts has cytotoxic effects against different types of cancer cell lines in vitro (Jafri et al, 2010;Bourgou et al, 2012;VSPK et al, 2013). Therefore, the present study was undertaken to provide comparative data on the in vitro cytotoxic activity of different extracts of N sativa seeds against A-549, a human lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It tends to metastasize outside the chest two-thirds of the time at clinical presentation, and approximately only 7% of patients are alive for 5 years since the beginning of treatment [20]. Recently, new agents such as erlotinib and bevacizuman, have been approved for the treatment of lung cancer, however the 5-year survival rate reaching 16% still remains the same [6]. On the contrary to other agents targeting single gene product, epigenetic drugs have chromatin as their target through the inhibition of histone deacetylases (HDAC'S) and DNA methyltransferases (DNMT'S) therefore, they may act upon most or all tumor types [4].…”
Section: Introductionmentioning
confidence: 99%